Glass fiber-reinforced polycarbonate resin composition, and molding comprising the same

JP2025025691APending Publication Date: 2025-02-21TEIJIN LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023130730
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0069】 本発明のガラス繊維強化ポリカーボネート樹脂組成物は、剛性、耐衝撃性、耐グリース性および外観に優れるため、住宅設備用途、建材用途、生活資材用途、インフラ設備用途、自動車用途、OA·EE用途、屋外機器用途およびその他の各種分野において幅広く有用であり、特に、これらの特性を高い次元で要求される電動工具外装部材用途において、極めて有用である。したがって本発明の奏する産業上の効果は極めて大である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025691000001
    Figure 2025025691000001
  • Figure 2025025691000002
    Figure 2025025691000002
Patent Text Reader

Abstract

To provide a glass fiber-reinforced polycarbonate resin composition excellent in rigidity, impact resistance, grease resistance, and external appearance, and a molding comprising the same.SOLUTION: A glass fiber-reinforced polycarbonate resin composition includes: a total 100 pts.wt of (A) 65-80 pts.wt of a polycarbonate resin (A constituent), and (B) 35-20 pts.wt of a resin constituent (B constituent) comprising 80-50 wt% of a polyethylene terephthalate resin (B-1 constituent) and 50-20 wt% of a polybutylene terephthalate resin (B-2 constituent); (C) 15-30 pts.wt of glass fibers (C constituent); and (D) 3-10 pts.wt of an impact-modifying agent (D constituent) having a core-shell structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass fiber reinforced polycarbonate resin composition having excellent rigidity, impact resistance, grease resistance and appearance, and to a molded article made from the same. [Background technology]

[0002] Polycarbonate resin has excellent mechanical properties, thermal properties, and self-extinguishing properties, and is therefore used in many applications, such as machine parts, automobile parts, electrical and electronic parts, and office equipment parts. A method of blending glass fibers is generally used to impart high rigidity and strength to polycarbonate resin. However, glass fiber reinforced polycarbonate resin has a high melt viscosity and low fluidity during injection molding, so it is prone to residual stress during molding and is prone to cracking when it comes into contact with chemicals such as grease. In addition, molded products made of glass fiber reinforced polycarbonate resin compositions are difficult to apply to applications requiring high-level appearance because the glass fibers float on the surface of the molded product. In order to solve the above problems, a method of melt-mixing polyester resin with glass fiber reinforced polycarbonate resin has been attempted. However, there is a problem in that the impact resistance is greatly reduced by melt-mixing polyester resin.

[0003] In order to solve such problems, a method of blending a core-shell type impact modifier having a butadiene rubber core into a molten mixture of polycarbonate resin, polybutylene terephthalate resin, and glass fiber (Patent Document 1) and a method of blending a core-shell type impact modifier having an acrylic rubber or silicone-acrylic composite rubber core into a molten mixture of polycarbonate resin, polyethylene terephthalate resin, and glass fiber (Patent Document 2) have been disclosed. However, when blending an impact modifier having a core-shell structure into a molten mixture of polycarbonate resin, polyester resin, and glass fiber, it is necessary to blend a large amount of the impact modifier having a core-shell structure in order to impart high impact resistance, so that the rigidity of the molded product is reduced and the appearance is greatly impaired due to color unevenness derived from the impact modifier having a core-shell structure. Therefore, it has been difficult to achieve high levels of rigidity, impact resistance, grease resistance, and appearance in a glass fiber reinforced polycarbonate resin composition. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Unexamined Patent Publication No. 64-11152 [Patent Document 2] JP 2010-261018 A Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above, an object of the present invention is to provide a glass fiber reinforced polycarbonate resin composition excellent in rigidity, impact resistance, grease resistance and appearance, and a molded article made from the same. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems and have found that a glass fiber-reinforced polycarbonate resin composition excellent in rigidity, impact resistance, grease resistance and appearance can be obtained by adding specific proportions of polyethylene terephthalate resin, polybutylene terephthalate resin, glass fiber and an impact modifier having a core-shell structure to a polycarbonate resin, and have thus completed the present invention.

[0007] According to the present invention, the above object is achieved by the following items 1 to 5. 1. A glass fiber reinforced polycarbonate resin composition characterized by containing, per 100 parts by weight in total, 65 to 80 parts by weight of (A) polycarbonate resin (A component) and 35 to 20 parts by weight of resin component (B component) consisting of 80 to 50% by weight of polyethylene terephthalate resin (B-1 component) and 50 to 20% by weight of polybutylene terephthalate resin (B-2 component), (C) 15 to 30 parts by weight of glass fiber (C component) and (D) 3 to 10 parts by weight of impact modifier having a core-shell structure (D component). 2. The glass fiber reinforced polycarbonate resin composition according to item 1 above, characterized in that component D is a graft polymer obtained by graft polymerizing at least one compound containing a (meth)acrylic acid ester compound onto at least one rubber selected from the group consisting of butadiene rubber, acrylic rubber, and silicone-acrylic composite rubber. 3. The glass fiber-reinforced polycarbonate resin composition according to item 2 above, wherein component D is a graft polymer obtained by graft polymerizing a (meth)acrylic acid ester compound and styrene onto a butadiene rubber. 4. A molded article obtained by molding the glass fiber reinforced polycarbonate resin composition according to any one of items 1 to 3 above. 5. The molded product according to the preceding paragraph 4, which is an exterior component for an electric power tool.

[0008] The present invention will be described in detail below. (Component A: polycarbonate resin) The polycarbonate resin used in the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. Examples of the reaction method include an interfacial polymerization method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound.

[0009] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)pentane, 4,4'-(p-phenylene) Examples of the dihydric phenol include 4,4'-(m-phenylenediisopropylidene)diphenol, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, bis(4-hydroxyphenyl)oxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, bis(4-hydroxyphenyl)ester, bis(4-hydroxy-3-methylphenyl)sulfide, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene. The preferred dihydric phenol is a bis(4-hydroxyphenyl)alkane, and among them, bisphenol A is particularly preferred from the viewpoint of impact resistance and is widely used.

[0010] In the present invention, in addition to bisphenol A-based polycarbonate resins, which are general-purpose polycarbonate resins, it is possible to use special polycarbonate resins produced using other dihydric phenols as the A component.

[0011] For example, polycarbonate resins (homopolymers or copolymers) using 4,4'-(m-phenylenediisopropylidene)diphenol (hereinafter sometimes abbreviated as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter sometimes abbreviated as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes abbreviated as "BCF") as part or all of the dihydric phenol components are suitable for applications where dimensional changes due to water absorption and dimensional stability are particularly demanding. These dihydric phenols other than BPA are preferably used in an amount of 5 mol% or more, particularly 10 mol% or more, of the total dihydric phenol components constituting the polycarbonate resin.

[0012] In particular, when high rigidity and better hydrolysis resistance are required, it is particularly suitable that the component A constituting the resin composition is a copolymer polycarbonate resin of the following (1) to (3). (1) A copolymerized polycarbonate resin in which, relative to 100 mol % of a dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %). (2) A copolymerized polycarbonate resin in which, relative to 100 mol % of a dihydric phenol component constituting the polycarbonate resin, BPA is 10 to 95 mol % (more preferably 50 to 90 mol %, and even more preferably 60 to 85 mol %) and BCF is 5 to 90 mol % (more preferably 10 to 50 mol %, and even more preferably 15 to 40 mol %). (3) A copolymer polycarbonate resin in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %).

[0013] These special polycarbonate resins may be used alone or in a suitable mixture of two or more kinds, or may be used in a mixture with a commonly used bisphenol A type polycarbonate resin.

[0014] The production methods and properties of these special polycarbonate resins are described in detail in, for example, JP-A-6-172508, JP-A-8-27370, JP-A-2001-55435, and JP-A-2002-117580.

[0015] Among the various polycarbonate resins mentioned above, those in which the copolymer composition and the like are adjusted to bring the water absorption rate and Tg (glass transition temperature) into the ranges described below have good hydrolysis resistance of the polymer itself and are also remarkably excellent in terms of low warpage after molding, and are therefore particularly suitable in fields where dimensional stability is required. (i) a polycarbonate resin having a water absorption rate of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180° C.; or (ii) A polycarbonate resin having a Tg of 160 to 250° C., preferably 170 to 230° C., and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, and more preferably 0.14 to 0.27%.

[0016] Here, the water absorption rate of the polycarbonate resin is a value measured by using a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm and immersing it in water at 23°C for 24 hours in accordance with ISO62-1980, and measuring the moisture content. Also, Tg (glass transition temperature) is a value determined by differential scanning calorimetry (DSC) measurement in accordance with JIS K7121.

[0017] The carbonate precursor may be a carbonyl halide, a carbonic acid diester or a haloformate, and specific examples thereof include phosgene, diphenyl carbonate or a dihaloformate of a dihydric phenol.

[0018] When the dihydric phenol and carbonate precursor are used to produce a polycarbonate resin by interfacial polymerization, a catalyst, a terminal terminator, an antioxidant for preventing oxidation of the dihydric phenol, etc. may be used as necessary. The polycarbonate resin of the present invention includes a branched polycarbonate resin copolymerized with a trifunctional or higher polyfunctional aromatic compound, a polyester carbonate resin copolymerized with an aromatic or aliphatic (including alicyclic) bifunctional carboxylic acid, a copolymerized polycarbonate resin copolymerized with a bifunctional alcohol (including alicyclic), and a polyester carbonate resin copolymerized with such a bifunctional carboxylic acid and a bifunctional alcohol. The polycarbonate resin may also be a mixture of two or more of the obtained polycarbonate resins.

[0019] The reaction modes of the method for producing the polycarbonate resin of the present invention, such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid-phase transesterification method and the ring-opening polymerization method of a cyclic carbonate compound, are well known in various literatures and patent publications.

[0020] The viscosity average molecular weight (M) of the polycarbonate resin is not particularly limited, but is preferably 1.8×10 4 ~4.0×10 4 and more preferably 2.0×10 4 ~3.5×10 4 , and more preferably 2.2×10 4 ~3.0×10 4 The viscosity average molecular weight is 1.8 × 10 4 Polycarbonate resins with a viscosity average molecular weight of less than 4.0×10 may not provide good mechanical properties. 4 Resin compositions obtained from polycarbonate resins exceeding this limit are inferior in terms of flowability during injection molding and therefore are inferior in versatility.

[0021] The viscosity average molecular weight in the present invention is calculated by the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin in 100 ml of methylene chloride. Specific viscosity (η SP )=(tt 0 ) / t 0 [t 0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall] The specific viscosity (η SP ) and calculate the viscosity average molecular weight M using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7

[0022] The viscosity average molecular weight of the polycarbonate resin in the glass fiber reinforced polycarbonate resin composition of the present invention is calculated as follows. That is, the composition is mixed with methylene chloride in an amount 20 to 30 times by weight, and the soluble matter in the composition is dissolved. The soluble matter is collected by filtration through Celite. The solvent in the resulting solution is then removed. The solid after the solvent removal is thoroughly dried to obtain a solid of components that dissolve in methylene chloride. 0.7 g of the solid is dissolved in 100 ml of methylene chloride to obtain a solution, and the specific viscosity at 20°C is determined in the same manner as above, and the viscosity average molecular weight M is calculated from the specific viscosity in the same manner as above.

[0023] As the polycarbonate resin of the present invention, a polycarbonate-polydiorganosiloxane copolymer resin can also be used.

[0024] Furthermore, polycarbonate resins that are recycled from used products, i.e., recycled polycarbonate resins, can also be used as polycarbonate resins.Preferably used products include various glazing materials such as soundproof walls, automobile windows, translucent roofing materials, and automobile sunroofs, transparent members such as windshields and automobile headlamp lenses, containers such as water bottles, light guide plates, eyeglass lenses, and optical recording media.Furthermore, crushed products obtained from non-conforming products, sprues, runners, etc., or pellets obtained by melting them can also be used.

[0025] (Component B: Resin component consisting of polyethylene terephthalate resin and polybutylene terephthalate resin) The resin composition of the present invention contains, as component B, a resin component consisting of a polyethylene terephthalate resin (component B-1) and a polybutylene terephthalate resin (component B-2).

[0026] (B-1 component: polyethylene terephthalate resin) The polyethylene terephthalate resin is a saturated polyester polymer or copolymer obtained by a condensation reaction of terephthalic acid or its ester-forming derivative as an aromatic dicarboxylic acid component and ethylene glycol or its ester-forming derivative as a diol component, and is a thermoplastic polyester resin containing ethylene terephthalate units as repeating units, preferably 70 mol% or more, more preferably 80 mol% or more. The polyethylene terephthalate resin is produced according to a conventional method by reacting the dicarboxylic acid component and the diol component with heating in the presence of a polycondensation catalyst containing titanium, germanium, antimony, etc., and discharging the by-product water or lower alcohol out of the system. At this time, either a batch method or a continuous method can be used for the polymerization, and it is also possible to increase the degree of polymerization by solid-state polymerization.

[0027] The end group structure of the polyethylene terephthalate resin used is not particularly limited, and the proportion of hydroxyl groups and carboxyl groups in the end groups may be approximately equal, or one of them may be more abundant. Furthermore, the end groups may be blocked by reacting with a compound reactive to the end groups.

[0028] In the present invention, the intrinsic viscosity of the polyethylene terephthalate resin is not limited, but is preferably in the range of 0.4 to 1.2. When the intrinsic viscosity is within this range, melt molding is easy, and the strength of the molded product obtained therefrom may be high. The intrinsic viscosity is more preferably in the range of 0.45 to 1.1, and even more preferably 0.5 to 1.0. The intrinsic viscosity of the polyethylene terephthalate resin is measured by dissolving the polyethylene terephthalate resin in o-chlorophenol at a temperature of 35°C.

[0029] (B-2 component: polybutylene terephthalate resin) Polybutylene terephthalate resin is obtained by polycondensation of terephthalic acid or its ester-forming derivative with an alkylene glycol having 4 carbon atoms or its ester-forming derivative. The polybutylene terephthalate resin may be a copolymer containing 70% or more by weight of the polybutylene terephthalate resin itself.

[0030] Examples of dibasic acid components other than terephthalic acid and its lower alcohol esters include aliphatic and aromatic polybasic acids such as isophthalic acid, naphthalenedicarboxylic acid, adipic acid, sebacic acid, trimellitic acid, and succinic acid, or ester-forming derivatives thereof. Examples of glycol components other than 1,4-butanediol include ordinary alkylene glycols, for example, ethylene glycol, diethylene glycol, propylene glycol, trimethylene glycol, hexamethylene glycol, neopentyl glycol, cyclohexanedimethanol, and lower alkylene glycols such as 1,3-octanediol, aromatic alcohols such as bisphenol A and 4,4'-dihydroxybiphenyl, alkylene oxide adduct alcohols such as 2-mol ethylene oxide adduct of bisphenol A and 3-mol propylene oxide adduct of bisphenol A, polyhydroxy compounds such as glycerin and pentaerythritol, or ester-forming derivatives thereof.

[0031] In the present invention, any of the polybutylene terephthalate resins produced by polycondensation of the above-mentioned compounds as monomer components can be used as component B-2 of the present invention, and they can be used alone or in combination of two or more kinds.

[0032] In the present invention, the intrinsic viscosity of the polybutylene terephthalate resin is not limited, but is preferably in the range of 0.6 to 1.4. When the intrinsic viscosity is within this range, melt molding is easy, and the strength of the molded product obtained therefrom may be high. The intrinsic viscosity is more preferably in the range of 0.65 to 1.3, and even more preferably 0.7 to 1.2. The intrinsic viscosity of the polybutylene terephthalate resin is measured by dissolving the polybutylene terephthalate resin in o-chlorophenol at a temperature of 25°C.

[0033] The content of component B is 35 to 20 parts by weight, preferably 32 to 22 parts by weight, and more preferably 29 to 24 parts by weight, per 100 parts by weight of the total of components A and B. If the content exceeds 35 parts by weight, the impact resistance decreases, and if it is less than 20 parts by weight, the grease resistance decreases and the floating of glass fibers becomes noticeable, making it impossible to obtain the desired appearance.

[0034] The contents of B-1 and B-2 components are 80-50% by weight of B-1 component and 50-20% by weight of B-2 component in 100% by weight of B component, preferably 75-55% by weight of B-1 component and 45-25% by weight of B-2 component, more preferably 70-60% by weight of B-1 component and 40-30% by weight of B-2 component. When the contents of B-1 and B-2 components in B component are within the above ranges, the impact resistance is significantly improved without blending a large amount of an impact modifier having a core-shell structure. When the content of B-1 component in B component is more than 80% by weight and the content of B-2 component is less than 20% by weight, the impact resistance is reduced and the lifting of glass fibers becomes noticeable. When the content of B-1 component in B component is less than 50% by weight and the content of B-2 component is more than 50% by weight, the impact resistance is reduced.

[0035] (Component C: Glass fiber) The resin composition of the present invention contains glass fibers as component C. Suitable examples of the glass fibers used in the present invention include glass fibers having a round cross section and flat cross-sectional glass fibers having an average major axis of 7 to 50 μm and an average ratio of major axis to minor axis (major axis / minor axis) of 1.5 to 8.

[0036] The glass composition of the above glass fiber is not particularly limited and may be any of various glass compositions such as A-glass, C-glass, and E-glass. Such glass fiber may contain TiO 2 , S.O. 3 , and P 2 O 5 The glass fibers may contain components such as fluorine, fluorine-based resin, styrene resin, acrylic resin, polyester resin, epoxy resin, urethane resin, etc. Among these, E glass (alkali-free glass) is more preferable. From the viewpoint of improving mechanical strength, such glass fibers are preferably surface-treated with a known surface treatment agent, such as a silane coupling agent, a titanate coupling agent, or an aluminate coupling agent. Also, those that have been bundled with an olefin resin, a styrene resin, an acrylic resin, a polyester resin, an epoxy resin, or a urethane resin are preferable. The amount of the sizing agent attached to the bundled glass fibers is preferably 0.1 to 3% by weight, more preferably 0.2 to 1% by weight, based on 100% by weight of the glass fibers.

[0037] The content of component C is 15 to 30 parts by weight, preferably 16 to 27 parts by weight, and more preferably 17 to 24 parts by weight, per 100 parts by weight of the total of components A and B. If the content of component C is less than 15 parts by weight, the rigidity is insufficient. On the other hand, if the content exceeds 30 parts by weight, the impact resistance decreases and the floating of glass fibers becomes noticeable, making it impossible to obtain the desired appearance.

[0038] (Component D: Impact modifier with core-shell structure) The glass fiber reinforced polycarbonate resin composition of the present invention contains an impact modifier having a core-shell structure as component D. The impact modifier having a core-shell structure is a graft copolymer in which a rubber component having a glass transition temperature of 10° C. or less is copolymerized as a core and one or more monomers selected from (meth)acrylic acid ester compounds and aromatic vinyl compounds are copolymerized as a shell.

[0039] Examples of the rubber component of component D include butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber, silicone-acrylic composite rubber, isobutylene-silicone composite rubber, isoprene rubber, styrene-butadiene rubber, chloroprene rubber, ethylene-propylene rubber, nitrile rubber, ethylene-acrylic rubber, silicone rubber, epichlorohydrin rubber, fluororubber, and those in which hydrogen has been added to the unsaturated bond portion. The glass transition temperature of the rubber component is preferably -10°C or lower, more preferably -30°C or lower, and from these points of view, butadiene rubber, acrylic rubber, and silicone-acrylic composite rubber are preferred as the rubber component. Composite rubber refers to rubber in which two types of rubber components are copolymerized, or rubber polymerized to form an IPN structure in which the components are intertwined with each other so that they cannot be separated.

[0040] Examples of the (meth)acrylic acid ester compound copolymerized as a shell with the D component include methyl acrylate, ethyl acrylate, butyl acrylate, cyclohexyl acrylate, octyl acrylate, etc., and examples of the methacrylic acid ester include methyl methacrylate, ethyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, octyl methacrylate, etc., with methyl methacrylate being particularly preferred. Although not particularly limited, the (meth)acrylic acid ester is preferably contained in an amount of 10% by weight or more, more preferably 15% by weight or more, based on 100% by weight of the graft component (based on 100% by weight of the shell in the case of a core-shell polymer).

[0041] Examples of the aromatic vinyl compound that is copolymerized with component D as a shell include styrene, α-methylstyrene, p-methylstyrene, alkoxystyrene, and halogenated styrene.

[0042] In the present invention, it is most preferable to compound a graft polymer obtained by graft polymerizing a (meth)acrylic acid ester compound and styrene with a butadiene rubber, since this can further increase the impact resistance of the resulting molded article.

[0043] The content of component D is 3 to 10 parts by weight, preferably 4 to 9 parts by weight, and more preferably 5 to 8 parts by weight, per 100 parts by weight of the total of components A and B. If the content of component D is less than 3 parts by weight, sufficient impact resistance and grease resistance cannot be obtained, and if it exceeds 10 parts by weight, the rigidity decreases and color unevenness due to component D becomes noticeable, making it impossible to obtain the desired appearance.

[0044] (Other additives) (i) Phosphorus-based stabilizers, phenol-based stabilizers, other heat stabilizers It is preferable that various heat stabilizers are blended in the resin composition of the present invention. Phosphorus-based stabilizers are suitable as such heat stabilizers. Examples of phosphorus-based stabilizers include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphines. Such phosphorus-based stabilizers can be used alone or in combination of two or more. Examples of phosphite compounds include trialkyl phosphites such as tridecyl phosphite, dialkyl monoaryl phosphites such as didecyl monophenyl phosphite, monoalkyl diaryl phosphites such as monobutyl diphenyl phosphite, triaryl phosphites such as triphenyl phosphite and tris(2,4-di-tert-butylphenyl)phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol, and the like. Examples of the phosphate compound include pentaerythritol phosphites such as bis(2,4-dicumylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and cyclic phosphites such as 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite and 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite. Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, triethyl phosphate, diphenylcresyl phosphate, diphenylmonoorthoxenyl phosphate, tributoxyethyl phosphate, and diisopropyl phosphate, and preferably triphenyl phosphate and trimethyl phosphate. Preferred examples of the phosphonite compound include tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenyl phosphonite, and more preferred are tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenyl phosphonite.Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are preferred. Examples of the phosphonate compounds include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate. Examples of the tertiary phosphine include triphenylphosphine.

[0045] The content of such phosphorus-based stabilizer is preferably 0.001 to 3.0 parts by weight, more preferably 0.01 to 2.0 parts by weight, and even more preferably 0.05 to 1.0 part by weight, per 100 parts by weight of the total of the A component and the B component.

[0046] Examples of the phenol-based stabilizer include hindered phenol compounds. As the hindered phenol compound, various compounds that are usually blended into resins can be used. Examples of such hindered phenol compounds include α-tocopherol, butyl hydroxytoluene, sinapyl alcohol, vitamin E, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5-di-tert-butyl- 4-Hydroxybenzylphosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylene-bis(6-α-methyl-benzyl-p-cresol), 2,2'-ethylidene-bis(4,6-di-tert-butyl phenol), 2,2'-butylidene-bis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2-tert-butyl-4-methyl-6-(3-tert-butyl-5 -methyl-2-hydroxybenzyl)phenyl]terephthalate, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-Di-tert-butyl-4-hydroxybenzyl) sulfide, 4,4'-di-thiobis(2,6-di-tert-butylphenol), 4,4'-tri-thiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylene bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylene bis-(3,5- Di-tert-butyl-4-hydroxyhydrocinnamide), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanurate, tris(3,5-di-tert-butyl 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate, 1,3,5-tris2[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanurate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylene n-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetate, 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, 1,3,5-trimethyl-2,4,Examples of the compounds include 6-tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)benzene and tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)isocyanurate. Among the above compounds, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane are preferably used in the present invention. Particularly preferred is 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane. The above hindered phenol-based antioxidants can be used alone or in combination of two or more kinds.

[0047] The content of the phenol-based stabilizer is preferably 0.001 to 3.0 parts by weight, more preferably 0.01 to 2.0 parts by weight, and even more preferably 0.05 to 1.0 part by weight, relative to 100 parts by weight of the total of the A component and the B component.

[0048] The resin composition of the present invention may also contain other heat stabilizers than the phosphorus-based stabilizer and phenol-based stabilizer. Such other heat stabilizers are preferably used in combination with either one of these stabilizers and the antioxidant, and particularly preferably with both. Suitable examples of such other heat stabilizers include lactone-based stabilizers such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene (details of such stabilizers are described in JP-A-7-233160). Such a compound is commercially available as Irganox HP-136 (trademark, manufactured by CIBA SPECIALTY CHEMICALS), and this compound can be used. Furthermore, stabilizers in which this compound is mixed with various phosphite compounds and hindered phenol compounds are commercially available. Suitable examples include Irganox HP-2921 manufactured by the above company. Such premixed stabilizers can also be used in the present invention. The amount of the lactone-based stabilizer to be added is preferably 0.0005 to 0.05 parts by weight, and more preferably 0.001 to 0.03 parts by weight, per 100 parts by weight of the total of the A component and the B component.

[0049] Other examples of the heat stabilizer include sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-laurylthiopropionate), and glycerol-3-stearylthiopropionate. Such heat stabilizers are particularly effective when the resin composition is applied to rotational molding. The amount of such sulfur-containing stabilizers is preferably 0.001 to 0.1 parts by weight, more preferably 0.01 to 0.08 parts by weight, based on 100 parts by weight of the total of the A component and the B component.

[0050] (ii) Ultraviolet absorber The glass fiber reinforced polycarbonate resin composition of the present invention may contain an ultraviolet absorbing agent, such as benzophenone-based, benzotriazole-based, hydroxyphenyltriazine-based, and cyclic iminoester-based compounds.

[0051] Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester. The above ultraviolet absorbents can be used alone or in combination of two or more kinds.

[0052] (iii) Hindered amine light stabilizers The glass fiber reinforced polycarbonate resin composition of the present invention may contain a hindered amine light stabilizer. Hindered amine light stabilizers are generally called HALS (Hindered Amine Light Stabilizers), and are compounds having a 2,2,6,6-tetramethylpiperidine skeleton in their structure.

[0053] Hindered amine light stabilizers are broadly divided into three types based on the bonding partner of the nitrogen atom in the piperidine skeleton: NH type (hydrogen bonded to the nitrogen atom), NR type (alkyl group (R) bonded to the nitrogen atom), and N-OR type (alkoxy group (OR) bonded to the nitrogen atom). From the viewpoint of the basicity of the hindered amine light stabilizer, it is more preferable to use the NR type or N-OR type, which have low basicity, when applying it to polycarbonate resin. The hindered amine light stabilizers can be used alone or in combination of two or more kinds.

[0054] (iv) Mold release agent It is preferable to further blend a mold release agent in the glass fiber reinforced polycarbonate resin composition of the present invention for the purpose of improving the productivity during molding and reducing distortion of the molded product. As such a mold release agent, a known one can be used. For example, saturated fatty acid ester, unsaturated fatty acid ester, polyolefin wax (polyethylene wax, 1-alkene polymer, etc., modified with a functional group-containing compound such as acid modification can also be used), silicone compound, fluorine compound (fluorine oil represented by polyfluoroalkyl ether, etc.), paraffin wax, beeswax, etc. can be mentioned. Among them, fatty acid ester and polyolefin wax can be mentioned as a preferable mold release agent.

[0055] (v) Dyes and pigments The glass fiber reinforced polycarbonate resin composition of the present invention can further contain various dyes and pigments to provide molded products with a variety of designs. By blending a fluorescent whitening agent or other fluorescent dyes that emit light, it is possible to impart even better design effects by taking advantage of the emitted color. It is also possible to provide a glass fiber reinforced polycarbonate resin composition that is colored with a very small amount of dyes and pigments and has vivid color development.

[0056] (vi) Filling material In the glass fiber reinforced polycarbonate resin composition of the present invention, various fillers other than glass fibers can be blended within the range in which the effects of the present invention are exhibited. For example, silicate minerals, calcium carbonate, glass beads, glass balloons, glass flakes, carbon fibers, carbon flakes, carbon beads, carbon milled fibers, graphite, vapor-phase grown ultrafine carbon fibers (fiber diameter less than 0.1 μm), carbon nanotubes (fiber diameter less than 0.1 μm, hollow), fullerenes, metal flakes, metal fibers, metal-coated glass fibers, metal-coated carbon fibers, metal-coated glass flakes, silica, metal oxide particles, metal oxide fibers, metal oxide balloons, and various whiskers (potassium titanate whiskers, aluminum borate whiskers, basic magnesium sulfate, etc.). These reinforcing fillers may be included in combination of one type or two or more types.

[0057] (vii) Flame retardants Various compounds conventionally known as flame retardants for thermoplastic resins, particularly aromatic polycarbonate resins, can be applied to the glass fiber reinforced polycarbonate resin composition of the present invention, but more preferably, halogen-based flame retardants (e.g., brominated polycarbonate compounds, etc.), phosphorus-based flame retardants (e.g., monophosphate compounds, phosphate oligomer compounds, phosphonate oligomer compounds, phosphonitrile oligomer compounds, phosphonic acid amide compounds, and phosphazene compounds, etc.), metal salt-based flame retardants (e.g., organic sulfonic acid alkali (earth) metal salts, boric acid metal salt-based flame retardants, and stannic acid metal salt-based flame retardants, etc.), and silicone-based flame retardants consisting of silicone compounds. The incorporation of compounds used as flame retardants not only improves the glass fiber reinforcement, but also improves, for example, antistatic properties, fluidity, rigidity, and thermal stability based on the properties of each compound.

[0058] (viii) Anti-drip agents The glass fiber reinforced polycarbonate resin composition of the present invention may contain an anti-drip agent. By containing this anti-drip agent, good glass fiber reinforcement can be achieved without impairing the physical properties of the molded article.

[0059] The drip prevention agent may be a fluorine-containing polymer having fibril-forming ability, and examples of such a polymer include polytetrafluoroethylene, tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), partially fluorinated polymers as shown in U.S. Patent No. 4,379,910, polycarbonate resins produced from fluorinated diphenols, etc. Among these, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE) is preferred.

[0060] In addition, in the present invention, coated branched PTFE can be used as the drip prevention agent. The coated branched PTFE is a polytetrafluoroethylene mixture consisting of branched polytetrafluoroethylene particles and an organic polymer, and has a coating layer consisting of an organic polymer, preferably a polymer containing a unit derived from a styrene monomer and / or a unit derived from an acrylic monomer, on the outside of the branched polytetrafluoroethylene. The coating layer is formed on the surface of the branched polytetrafluoroethylene. In addition, the coating layer preferably contains a copolymer of a styrene monomer and an acrylic monomer.

[0061] (ix) Other additives In addition, the glass fiber reinforced polycarbonate resin composition of the present invention may contain small amounts of known additives in order to impart various functions to the molded product or to improve the properties of the molded product. These additives are added in normal amounts as long as they do not impair the object of the present invention.

[0062] Such additives include sliding agents (e.g., PTFE particles), colorants (e.g., pigments such as carbon black and titanium oxide, and dyes), light diffusing agents (e.g., acrylic crosslinked particles, silicone crosslinked particles, extremely thin glass flakes, calcium carbonate particles), antistatic agents, crystal nucleating agents, inorganic and organic antibacterial agents, photocatalytic antifouling agents (e.g., fine particle titanium oxide, fine particle zinc oxide), radical generators, infrared absorbing agents (heat ray absorbing agents), and photochromic agents.

[0063] (Production of glass fiber reinforced polycarbonate resin composition) Any method can be used to produce the glass fiber reinforced polycarbonate resin composition of the present invention. For example, the A to D components and any other additives are thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, or an extrusion mixer, and then the premix is ​​granulated using an extrusion granulator or a briquetting machine, if necessary, and then melt-kneaded using a melt mixer such as a vented twin-screw extruder, and then pelletized using a pelletizer. Other examples include a method in which each component is independently supplied to a melt mixer such as a vented twin-screw extruder, and a method in which a portion of each component is premixed and then supplied to a melt mixer independently of the remaining components.

[0064] The extruder preferably has a vent capable of degassing moisture in the raw materials and volatile gases generated from the melt-kneaded resin. A vacuum pump is preferably installed from the vent to efficiently discharge the generated moisture and volatile gases to the outside of the extruder. It is also possible to install a screen in a zone before the extruder die section to remove foreign matter mixed in the extrusion raw materials, thereby removing the foreign matter from the resin composition. Examples of such a screen include a wire mesh, a screen changer, and a sintered metal plate (such as a disk filter).

[0065] Examples of the melt kneader include a twin-screw extruder, a Banbury mixer, a kneading roll, a single-screw extruder, and a multi-screw extruder having three or more screws.

[0066] The resin extruded as described above is directly cut and pelletized, or strands are formed and then the strands are cut by a pelletizer and pelletized. When it is necessary to reduce the influence of external dust during pelletization, it is preferable to purify the atmosphere around the extruder. Furthermore, in the production of such pellets, various methods already proposed for polycarbonate resins for optical disks can be used to narrow the shape distribution of the pellets, reduce miscuts, reduce fine powder generated during transportation or shipping, and reduce bubbles (vacuum bubbles) generated inside the strands or pellets. These prescriptions can achieve high cycle molding and reduce the rate of defects such as silver. The shape of the pellets can be a general shape such as a cylinder, a prism, or a sphere, but is more preferably a cylinder. The diameter of such a cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and even more preferably 2 to 3.3 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and even more preferably 2.5 to 3.5 mm.

[0067] (Molded article made from the glass fiber reinforced polycarbonate resin composition of the present invention) The glass fiber reinforced polycarbonate resin composition of the present invention can be injection molded into various products by using pellets obtained by the above-mentioned method. In such injection molding, molded products can be obtained using not only ordinary molding methods but also injection molding methods such as injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including injection of supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding, and ultra-high speed injection molding, depending on the purpose. The advantages of these various molding methods are already widely known. In addition, molding can be performed using either a cold runner method or a hot runner method.

[0068] The glass fiber reinforced polycarbonate resin composition of the present invention can also be used in the form of various profile extrusion molded products, sheets, films, etc. by extrusion molding. For molding sheets and films, inflation method, calendar method, casting method, etc. can also be used. Furthermore, it can be molded into a heat shrinkable tube by subjecting it to a specific stretching operation. The resin composition of the present invention can also be molded into a molded product by rotational molding, blow molding, etc. Effect of the Invention

[0069] The glass fiber reinforced polycarbonate resin composition of the present invention is excellent in rigidity, impact resistance, grease resistance and appearance, and is therefore widely useful in housing equipment, building materials, daily necessities, infrastructure equipment, automobiles, office automation and electronics, outdoor equipment and other various fields, and is particularly useful in the application of exterior members of electric power tools, which require these properties at a high level. Therefore, the industrial effects of the present invention are extremely large. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0070] The present inventors currently consider the best form of the invention to be one that embodies the preferred ranges of each of the above-mentioned requirements, and representative examples thereof are described in the following examples, although the present invention is not limited to these forms. EXAMPLES

[0071] The embodiment of the present invention is a summary of the preferred ranges of each of the above-mentioned requirements, and representative examples are described in the following examples. Of course, the present invention is not limited to these embodiments. Evaluations were performed by the following methods. The results are shown in Tables 1 and 2.

[0072] (i) Rigidity The flexural modulus was measured in accordance with ISO178 using ISO flexural test pieces obtained by the method described below.

[0073] (ii) Impact resistance A DuPont impact test was carried out using a test piece with a length of 150 mm, width of 150 mm, and thickness of 2 mm obtained by the following method. The fracture energy of the test piece was calculated from the height at which a crack occurred when a 1 kg impact core (tip R = 4.5) was dropped directly below the test piece.

[0074] (iii) Grease resistance Using ISO tensile test pieces obtained by the method described below, a 1% strain was applied using a three-point bending test method, and then Multemp SRL (grease for ball bearings, manufactured by Kyodo Yushi Co., Ltd.) was applied and the pieces were left at 23°C for 168 hours, after which the presence or absence of any change in appearance was confirmed. The evaluation was performed according to the following criteria. ○: No change in appearance was observed. ×: Fine cracks and large cracks that may lead to fracture are observed.

[0075] (iv) Appearance (iv-i) Glass fiber float The glass fibers on the surface of a sample plate (a three-level plate with holes) prepared by the method described below were visually evaluated. The evaluation was performed according to the following criteria. ○: Glass fiber floating is not noticeable. △: Glass fiber is slightly noticeable. ×: Glass fibers are clearly visible.

[0076] (iv-ii) Color unevenness due to impact modifiers with a core-shell structure The color unevenness on the surface of a sample plate (a three-level plate with holes) for evaluating color unevenness due to the impact modifier having a core-shell structure produced by the method described below was visually evaluated. The evaluation was performed according to the following criteria. ○: Color unevenness caused by the impact modifier is not noticeable. △: Color unevenness caused by the impact modifier is slightly noticeable. ×: Color unevenness caused by the impact modifier is clearly noticeable.

[0077] [Examples 1 to 11, Comparative Examples 1 to 8] The mixture was fed from the first feed port of the extruder with the composition shown in Tables 1 and 2. The feed rate of the mixture was precisely measured by a weighing scale [CWF manufactured by Kubota Corporation]. The extrusion was performed using a vented twin-screw extruder (TEX30α-38.5BW-3V manufactured by Japan Steel Works, Ltd.) with a diameter of 30 mmφ, with a screw rotation speed of 230 rpm, a discharge rate of 25 kg / h, and a vent vacuum of 3 kPa to obtain pellets by melt kneading. The extrusion temperature was 270°C from the first feed port to the die portion. The obtained pellets were dried in a hot air circulation dryer at 90 to 100°C for 6 hours, and then molded into test pieces for evaluation (ISO bending test pieces, ISO tensile test pieces, test pieces with a length of 150 mm, width of 150 mm, and thickness of 2 mm, and a sample plate (three-stage plate with holes)) using an injection molding machine at a cylinder temperature of 270°C and a mold temperature of 70°C. In addition, in order to evaluate color unevenness resulting from the impact modifier having a core-shell structure, carbon black (ROYAL BLACK RB90003S (product name) manufactured by Koshigaya Chemical Industries, Ltd.) was added to each composition, and a sample plate (three-step plate with holes) was prepared in the same manner as above. The symbols used for each component in Tables 1 and 2 are as follows:

[0078] (Component A) A-1: Aromatic polycarbonate resin (polycarbonate resin powder with a viscosity average molecular weight of 22,400 made by a conventional method from bisphenol A and phosgene, manufactured by Teijin Ltd., Panlite L-1225WP (product name)) (B-1 component) B-1-1: Polyethylene terephthalate resin (intrinsic viscosity 0.77, Teijin Limited, product name TRN-8550FF) (B-2 component) B-2-1: Polybutylene terephthalate resin (intrinsic viscosity 1.07, Polyplastics Co., Ltd., Duranex 700FP-EF201X (product name)) (C component) C-1: Circular cross-section chopped glass fiber (fiber diameter 13 μm, cut length 3 mm, Nitto Boseki Co., Ltd. CSG 3PE-455 (product name)) (D component) D-1: Impact modifier with a core-shell structure (the core is made of butadiene rubber, and the shell is a core-shell structure graft copolymer in which methyl methacrylate and styrene are graft polymerized, manufactured by Mitsubishi Chemical Corporation, Metablen E-870A (product name)) D-2: Impact modifier with a core-shell structure (core-shell structure graft copolymer in which the core is made of silicone-acrylic composite rubber and methyl methacrylate is graft-polymerized as the shell, manufactured by Mitsubishi Chemical Corporation, Metablen S-2030 (product name)) D-3: Impact modifier with a core-shell structure (a core-shell structure graft copolymer in which the core is made of acrylic rubber and methyl methacrylate is graft-polymerized, manufactured by Mitsubishi Chemical Corporation, Metablen W-600A (product name))

[0079] [Table 1]

[0080] [Table 2]

Claims

1. A glass fiber reinforced polycarbonate resin composition comprising 15 to 30 parts by weight of (C) glass fiber (component C) and 3 to 10 parts by weight of (D) an impact modifier having a core-shell structure (component D) per 100 parts by weight in total of 65 to 80 parts by weight of (A) polycarbonate resin (component A) and 35 to 20 parts by weight of a resin component (component B) consisting of 80 to 50% by weight of polyethylene terephthalate resin (component B-1) and 50 to 20% by weight of polybutylene terephthalate resin (component B-2).

2. 2. The glass fiber reinforced polycarbonate resin composition according to claim 1, wherein component D is a graft polymer obtained by graft polymerizing at least one compound containing a (meth)acrylic acid ester compound to at least one rubber selected from the group consisting of butadiene rubber, acrylic rubber, and silicone-acrylic composite rubber.

3. 3. The glass fiber-reinforced polycarbonate resin composition according to claim 2, wherein component D is a graft polymer obtained by graft polymerizing a (meth)acrylic acid ester compound and styrene onto a butadiene rubber.

4. A molded article obtained by molding the glass fiber reinforced polycarbonate resin composition according to any one of claims 1 to 3.

5. The molded article according to claim 4, which is an exterior member for an electric power tool.

Citation Information

Patent Citations

  • Thermoplastic polymer composition for exterior trim and exterior panel of automobile

    JP1989011152A

  • Polycarbonate / polyethylene terephthalate composite resin composition, and molded product

    JP2010261018A